Praktikalitas Training Kits HMI Berbasis Outseal PLC pada Pembelajaran Sistem Kontrol Terprogram - Yoga Maulana Putra; Risfendra Risfendra (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
The research was carried out with the aim of knowing the practical value of learning media training kits Human Machine Interface (HMI) based on Outseal PLC on programmed control system subjects at SMK Negeri 2 Payakumbuh. The implementation of the research to obtain practicality data comes from assessments conducted by 3 programmed control system subject teachers and 26 class XII Industrial Automation Engineering students. The valuation data collection technique is used by filling out practicality instruments that have previously been validated. The practicality instrument consists of 30 statement items using 5 rating scales. The results of data collection from teachers and students will then be tabulated and a descriptive analysis will be carried out to draw practicality assessment conclusions. The results research conducted revealed that the teacher's assessment of the level of practicality of training kits learning media was in the very practical category. While the results of the assessment conducted by the training kits students have a very practical level of effectiveness. So that it can be concluded that the learning media for HMI training kits based on Outseal PLC are very practical to use in learning programmed control systems for class XII at SMK Negeri 2 Payakumbuh.